Teledentistry and forensic odontology: Cross-sectional observational comparative pilot study. (September 2021) - Giraudeau, N.; Duflos, C.; Moncayo, C.; Marin, G.; Baccino, E.; Martrille, L.; Inquimbert, C.
Highlights: Teledentistry in forensic dentistry should be developed in the next few years. The organisational acceptability of teledentistry has to be studied. Implementation of teledentistry in forensic dentistry needs forensic dentists Abstract: Forensic dentistry is the branch of forensic science concerned with the study of teeth and jaws. To facilitate the work of experts, new comparative identification tools are emerging, with digital techniques such as the intra-oral camera, which are revolutionising current techniques in forensic dentistry. Objective: The aim of this study is to evaluate the diagnostic quality of the post-mortem odontogram carried out remotely via a video of the oral cavity using an intra-oral camera. The gold standard is the post-mortem odontogram obtained via the standard identification technique during the clinical examination. Materials and methods: 25 deceased patients were included in the study and the data were collected in the Forensic Medicine and Thanatology Department at the University Hospital of Montpellier. The protocol was divided into three stages: the gold standard consultation, the recording of videos with the Soprocare® camera, and the remote analysis of the images obtained. The gold standard consultation and the remote analysis were carried out by two separate dental surgeons responsible for completing a clinical file, used to establish the odontogram of the deceased patient. Results: The study was carried out on 25 deceased subjects, between 13 May and 12 June 2019. Our sample was composed of 68% men and 32% women. A sensitivity threshold of 0.97 was observed for the performance of the odontogram, i.e., for all the teeth actually present in the mouth for all subjects in the study, 97% of them were identified with the videos taken using the intraoral camera. The examination with the intra-oral camera demonstrated a good diagnostic performance in the detection of missing teeth with a PPV of 97.9% and a NPV of 98.2%. Practitioner became more skilled at recording the videos with the intra-oral camera. One can therefore note an ease in the handling of this digital tool, which gradually improved with the number of subjects included in the study Conclusions: The Soprocare® intraoral camera has an acceptable diagnostic validity in establishing the odontogram of the deceased. It enables fundamental elements to be detected with optimal efficiency. However, several points still need to be improved, in order to make the use of the camera during data collection as easy and efficient as possible.